Facilitating safe transition to home for preterm infants (FAST home): Protocol for a retrospective observational study. - Lisa Szatkowski; Janine Abramson; Sha Tao; Sarah E Seaton; Jon Dorling; Michelle Arellano-Meza; Jane Harvey; Tom Harvey; Shalini Ojha (PLoS ONE)
Background Preterm infants (i.e., those born before 37 completed weeks of pregnancy) often require additional care and are admitted to neonatal units soon after birth. Readiness for discharge home typically requires a level of physiological maturity such that an infant is able to: 1) breathe spontaneously without additional support; 2) maintain their own body temperature; 3) take all their nutritional requirements orally; 4) weighs ≥ 1700g and is gaining weight. Longer hospital stays than necessary can be detrimental to infants, stressful for families, and costly. Currently, little is known about whether, how long and why preterm infants stay in hospital beyond physiological readiness for discharge. Materials and methods We will conduct a retrospective cohort study using data from the National Neonatal Research Database on all infants born at < 37 weeks' gestational age (GA) admitted to neonatal units in England and Wales from 2016-2022. The day of life and postmenstrual age infants reach each physiological milestone, and the final barrier to discharge, will be identified. We will assess whether the final barrier differs by GA and between neonatal Operational Delivery Networks and summarise the number of days infants remain in hospital after surpassing all physiological milestones. We will explore the characteristics of infants, mothers and neonatal units associated with extended hospital stays beyond physiological readiness for discharge. Discussion The results of this study will allow identification of areas to target to help achieve a safe reduction in length of hospital stay and will support the development of evidence-based recommendations to guide optimal discharge practices. Trial registration ClinicalTrials.gov NCT06284044.